2004
DOI: 10.1007/s10096-004-1136-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of amphotericin B, fluconazole and voriconazole against 162 Cryptococcus neoformans isolates from Africa and Cambodia

Abstract: In order to determine the potential role that various antifungal agents might have in the management of cryptococcosis in tropical areas, the in vitro susceptibility of Cryptococcus neoformans isolates from Africa ( n=52) and Cambodia ( n=110) to three antifungal agents (amphotericin B, fluconazole and voriconazole) were compared using the E-test method. The results of this study (i) confirm the value of the E-test for testing the in vitro susceptibility of C. neoformans towards voriconazole; (ii) provide the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 13 publications
1
26
1
2
Order By: Relevance
“…13 A study from Malaysia showed low MIC 50 and MIC 90 (0.25/0.38 μg/mL). A similar result was reported from Taiwan, where the MIC 90 and susceptibility ranges were 0.5 (0.125-1) μg/mL, in agreement with results obtained by Chandenier et al, 14 who reported that both Asian and African isolates are susceptible to amphotericin B, whose MIC values did not exceed 0.125 μg/mL against the tested isolates. However, the results reported here show a slightly higher MIC than previous studies, with the MIC 90 and susceptibility ranges of 1 (0.0625-1) μg/mL, respectively.…”
supporting
confidence: 91%
“…13 A study from Malaysia showed low MIC 50 and MIC 90 (0.25/0.38 μg/mL). A similar result was reported from Taiwan, where the MIC 90 and susceptibility ranges were 0.5 (0.125-1) μg/mL, in agreement with results obtained by Chandenier et al, 14 who reported that both Asian and African isolates are susceptible to amphotericin B, whose MIC values did not exceed 0.125 μg/mL against the tested isolates. However, the results reported here show a slightly higher MIC than previous studies, with the MIC 90 and susceptibility ranges of 1 (0.0625-1) μg/mL, respectively.…”
supporting
confidence: 91%
“…The overall trend was that ECVs for C. neoformans molecular types were lower than those for C. gattii. Previous MIC 90 s and modes of these three triazoles have been similar (9,10,23,44,50). Because the distributions in CLSI YNB originated from a single laboratory, ECVs were not proposed for these distributions (Tables 2, 3, and 5).…”
Section: Resultsmentioning
confidence: 99%
“…CBPs are based on MIC distributions, pharmacokinetic and pharmacodynamic (PK/PD) parameters, animal studies, and clinical outcomes to therapy, while the ECV is based mostly on MIC distributions. Numerous surveys indicate that CLSI MICs are Յ16 g/ml (fluconazole) and Յ0.5 g/ml (the other three triazoles) for most C. neoformans and C. gattii isolates (5,9,10,16,24,43,50). In the last few years, azole (mostly fluconazole) antifungal susceptibility differences have been reported for these two species and for their molecular types and serotypes (10,11,25,33,50,51).…”
mentioning
confidence: 99%
“…Most of these reports involve resistance to fluconazole emerging in the setting of meningitis in AIDS patients after long treatments or prophylaxis with fluconazole (7,8,34). Recent reports from Cambodia (12,44) and from India (16) have raised the concern of a more widespread increase in fluconazole resistance among C. neoformans, suggesting the need for greater vigilance and more-widespread surveillance.…”
mentioning
confidence: 99%